Giant clam conservation in Sabah: A need for the appreciation of the Bajau people’s traditional ecological knowledge - N A Abd-Ebrah; Robert Francis Peters (IOP Publishing Ltd, 2021)
Kima (Tridacna sp.) is a type of giant clam that can be found in Indo-West Pacific tropical coral reefs. It is endangered due to its excessive exploitation as a source of exotic food and the degradation of its habitat. The gazette of marine parks in Sabah is a positive modern conservation effort to reduce threats on endangered marine species especially those found in the northern part of Sabah. Integral to the conservation of giant clams within those marine parks is the appreciation of indigenous knowledge of once known sea gypsies i.e. the Bajau people. Current conservation methods at several sites in Sabah’s marine park had shown several challenges, which circulate tension among the economics of local communities. To explore the possibility of appreciating indigenous knowledge into the conservation of giant clams, a scientific study with the objective of documenting traditional consumption method of the Bajau people was carried out. Direct observations and interviews on the local people were conducted, while descriptive statistics were used to analyse all collected data. Finding of this study shows the existence of traditional ecology knowledge (TEK) and traditional management among Bajau people pertinent to the conservation of Kima. TEK can complement conventional science and help to make more informed management decisions for clam conservation through for hybridization of modern and traditional management to customary management in managing and conserving giant clam population in Sabah’s marine parks. A synthesized advice to use traditional ecology knowledge as tool in developing more effective knowledge-inclusive partnerships between indigenous communities, researchers and policy decision-makers is provided in this article.